(untitled) (Colección, 2023)
The study of Machiavelli was recurrent in Louis Althusser. Machiavelli allowed him to rethink political action without supposing the a priori existence of a subject in whom Political Theory should axiomatically recognize the ability to carry out this action. This article aims to analyze the lecture Althusser gave in 1977 at the Institute of Political Sciences of Paris. Then, Althusser not only suggested this reading of Machiavelli, but also offered a non-cumulative conception of history, which enables a differentiated appropriation of Antiquity.